2013
DOI: 10.1097/mlr.0b013e31827808f6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease Management for Recently Homeless Veterans

Abstract: Background Though vulnerable populations may benefit from in-home health information technologies (HIT) that promote disease self-management, there is a “digital divide” in which these groups are often unlikely to use such programs. We describe the early phases of applying and testing an existing Veterans Administration (VA) HIT care management program, Care Coordination Home Telehealth (CCHT), to recently homeless Veterans in the U.S. Department of Housing and Urban Development-VA Supportive Housing (HUD-VASH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Satisfaction was directly related to the participant’s perceived relevance of the tools and the level of positivity in the relationship with the intervention provider. In two studies,30 31patients expressed high levels of satisfaction from their interaction with nurses, which promoted better understanding of their condition. Others showed high levels of willingness among patients to use telemonitoring equipment (95%) and recommend it to others (90%) or pay for telehealth services32 and a sense that equipment helped them to monitor and improve their health 33…”
Section: Resultsmentioning
confidence: 99%
“…Satisfaction was directly related to the participant’s perceived relevance of the tools and the level of positivity in the relationship with the intervention provider. In two studies,30 31patients expressed high levels of satisfaction from their interaction with nurses, which promoted better understanding of their condition. Others showed high levels of willingness among patients to use telemonitoring equipment (95%) and recommend it to others (90%) or pay for telehealth services32 and a sense that equipment helped them to monitor and improve their health 33…”
Section: Resultsmentioning
confidence: 99%
“…The search process refined the research question to examine the effectiveness of IPS with a homeless population. The search also revealed that IPS is currently being used with the homeless for various health interventions: TB, HIV, overdose prevention, and Hepatitis (Gabrielian et al 2013 ; Tulsky et al 2000 ; Wright et al 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…Peers are currently aiding the homeless with health management, medication regimes, and acting as buffers for professionals (Deering et al 2009 ; Fogarty et al 2001 ; Gabrielian et al 2013 ; Pilote et al 1996 ; Rice et al 2012 ; Tulsky et al 2000 ). The literature examining the efficacy of this practice has been mostly supportive; various studies report that peers can help to reduce hospital admissions, relapses, increase coping skills, and improve overall quality of life for those with mental illness (Davidson et al 2006 ; Salzer 2002 ; Solomon 2004 ; Wallcraft et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 89 percent of veterans had a mobile phone and health was the second most common reason for using their phones [ 108 ]. For recently housed veterans, in-home health information technologies—including the Care Coordination Home Telehealth (CCHT) program—hold promise for closing some of the Availability gaps for veterans managing chronic illnesses [ 109 ].…”
Section: Barriers To Access and Interventions/tools By Dimensionmentioning
confidence: 99%